2020
DOI: 10.1186/s40359-020-00488-0
|View full text |Cite
|
Sign up to set email alerts
|

Marital separation and contact with primary healthcare services for mental health problems: a register-based study

Abstract: Background Marital separation is associated with mental health problems, but little is known about how this translates into healthcare use. In this study, we examine the relationship between marital separation and primary healthcare use for mental health problems. Methods We used data covering the period from 2005 to 2015 from the Norwegian Population Register, Statistics Norway’s Educational Registration System and the Norwegian Health Economics Database. Data were analyzed using logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Divorce is a stressful event which might cause mental and psychosomatic disorders, either in the short term or more permanently. While some studies have shown that mental distress increases during the last years preceding the partnership dissolution and declines after the break-up (Blekesaune, 2008 ; Ding et al, 2021 ; Kravdal & Wörn, 2023 ; Leopold, 2018 ; Van Scheppingen & Leopold, 2020 ), other studies have indicated more long term adverse health consequences of divorce on measures such as contact with primary healthcare services for mental health problems (Reneflot et al, 2020 ), mental distress (Mastekaasa, 1995 ), immune functioning (Kiecolt-Glaser et al, 1987 ) and physical illness (Kravdal & Wörn, 2023 ; Lorenz et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Divorce is a stressful event which might cause mental and psychosomatic disorders, either in the short term or more permanently. While some studies have shown that mental distress increases during the last years preceding the partnership dissolution and declines after the break-up (Blekesaune, 2008 ; Ding et al, 2021 ; Kravdal & Wörn, 2023 ; Leopold, 2018 ; Van Scheppingen & Leopold, 2020 ), other studies have indicated more long term adverse health consequences of divorce on measures such as contact with primary healthcare services for mental health problems (Reneflot et al, 2020 ), mental distress (Mastekaasa, 1995 ), immune functioning (Kiecolt-Glaser et al, 1987 ) and physical illness (Kravdal & Wörn, 2023 ; Lorenz et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Having lived a large part of life alone, which is most common among the never married, has been linked to a number of health problems (Davidsen et al, 2022 ; Kriegbaum et al, 2009 , 2011 ). Divorce and the underlying relationship problems may cause an immediate and possibly also longer-term deterioration of health (Kravdal & Wörn, 2023 ; Reneflot et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Modelo explicativo de duelo por divorcio propuesto por Kaslow Se especifica el proceso de duelo que experimentan la pareja antes, durante y después de la ruptura amorosa representa un malestar emocional y una disonancia cognitiva que afecta la calidad de vida de las personas (Owen et al, 2019;Reneflot et al, 2020).…”
Section: Figuraunclassified
“…Se debe tener en consideración que previo a la disolución marital muy probablemente existen niveles elevados de sintomatología depresiva ocasionada por la disfunción de mediana y larga data en la pareja (Lin et al, 2019), siendo un factor de riesgo para sufrir crisis de estrés transitorio varios años después de la detención marital (Reneflot et al, 2020). Dado los roles asignados y el contexto cultural, se considera que las mujeres tienen mayor predisposición a presentar deterioros a nivel cognitivo, atribuyéndose a la limitación en el acceso a recursos económicos, sociales y psicológicos (Brown et al, 2021), factores que determinan que la intervención de las crisis de divorcio, debe ser fomentada indistintamente de la edad de la pareja y los años de matrimonio.…”
Section: Introductionunclassified
“…It can lead to a healthier lifestyle, better sociomoral support, reduced psychological stress, and higher motivation to be healthy [ 2 4 ]. An unmarried status, including being widowed, divorced, or single, is associated with increased mental health problems, cardiovascular diseases, coronary heart disease, and stroke-related death [ 5 , 6 ]. Regarding malignancies, a strong association between marital status and participation in cancer screening has been reported, and participation is even higher in married individuals with a participating partner [ 7 ].…”
Section: Introductionmentioning
confidence: 99%